Improvement on Transient Response of the Speed Control Circuit with Integrated Voltage Control Method - Irie, Hisaichi; Okui, Hideyuki (The Japan Institute of Power Electronics, 1994)
The DC chopper with Integrated voltage control method is stable and has no steady state error. The 2- or 4-quadrants DC chopper with this method have a lot of good characteristics, for example very simple control circuit and very rapid response. Applying this Integrated voltage control method, we constructed the speed control circuit for DC servo motor drive. This circuit has two feedback loops: the first one is a DC motor speed feedback loop and the second is a DC chopper output voltage feedback loop which is eliminated DC component by a coupling capacitor. In this speed control circuit, we can determine a damping factor of this control system freely if DC servo motor is over damping. Now we constructed the new speed control circuit for DC servo motor drive. This circuit has three feedback loops: the first one and the second are a speed feedback loop and a voltage feedback loop, the third is a current feedback loop. In this new speed control circuit, we can determine a damping factor of this new control system independently of the several damping factor of DC servo motor.